Beauveria bassiana pathogenicity to Diaphorina citri and compatibility of the fungus with phytosanitary products - Pinto, Ana Paula Ferreira; Batista Filho, Antonio; Almeida, José Eduardo Marcondes de; Wenzel, Inajá Marchizeli (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the pathogenicity of Beauveria bassiana to Diaphorina citri (Hemiptera: Psyllidae) nymphs, and to check the compatibility of the fungus with phytosanitary products, and its persistence in citrus plants. Nymphs of D. citri were sprayed with 5x106, 1x107, 5x107, 1x108, 5x108 and 1x109 conidia mL‑1 for lethal concentration determination. In order to evaluate the compatibility of the phytosanitary products with the fungus, neem extract and five insecticides of four different chemical groups were individually added to PDA culture medium, in which the fungus was cultivated. Vegetative growth, sporulation and viability of the entomopathogen were evaluated. In the greenhouse, citrus plants were first treated with the phytosanitary products and, then, with the pathogen. Exposure times of 24 hours, 7 and 14 days were evaluated. Fungus pathogenicity to D. citri nymphs was confirmed; LC50 of 0.4 x107 and LC90 of 6.7x107 conidia mL‑1 were determined at the tenth day of evaluation. In the laboratory, the phytosanitary products reduced fungus growth. In greenhouse, the products did not affect fungus survival on citrus plants.